Signal-Specialized Parameterization for Piecewise Linear Reconstruction - Tewari, Geetika; Snyder, John; Sander, Pedro V.; Gortler, Steven J.; Hoppe, Hugues (Eurographics Symposium on Geometry Processing (2004), 2004)
We propose a metric for surface parameterization specialized to its signal that can be used to create more efficient, high-quality texture maps. Derived from Taylor expansion of signal error, our metric predicts the signal approximation error - the difference between the original surface signal and its reconstruction from the sampled texture. Unlike previous methods, our metric assumes piecewise-linear reconstruction, and thus makes a good approximation to bilinear reconstruction employed in graphics hardware. We achieve significant savings in texture area for a desired signal accuracy compared to the signal-specialized parameterization metric proposed by Sander et al. in the 2002 Eurographics Workshop on Rendering